Terbangan Palembang in the Dimension of Electronic Music: A Study of the Creation of New Musical Works - Rio Eka Putra; Auzy Madona Adoma; Feri Firmansyah (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to explore andtransform the tradition of Terbangan Palembang, a form oftraditional religious music in South Sumatra, into the realm of electronic music ordigital music. This art form, which is usually performed in religious and social contexts usingTerbangan instruments, has distinctive rhythmic and vocal patterns. This studyuses an artistic practice approach with a creative method that includesthe stages of traditional sound exploration, digital manipulation, and electronic music composition. The collected traditional sounds are then manipulatedusing digital techniques such as sampling, looping, time-stretching, andthe addition of sound effects in digital audio workstation (DAW) software.The goal is to create new electronic music compositions that still containelements of the Terbangan identity but in a more contemporary andcontextual package in line with the times. The resulting work not only servesas a form of artistic expression, but also as a medium for the preservation andreactualization of local culture through a technological approach. This study showsthat local musical traditions can be creatively transformed without losingtheir spiritual and aesthetic value. In addition, tradition-based creationopens up space for the younger generation to recognize, appreciate, anddevelop the culture of their ancestors in a format that is more relevant to the digital age.